Hubungan Mekanisme Koping Dengan Tingkat Stres Pada Tahanan Di Rumah Tahanan Direktorat Tahanan Dan Barang Bukti Polda Kalteng - Septian Mugi Rahayu; Dian Mitra D.S; Rony Lukmansyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Coping mechanisms are an individual's ability to solve problems and respond to threatening situations. Stress is any situation that causes changes in a person's life so that forced to make adjustments to overcome it. The most important factor in resolving stress is the use of good coping mechanisms. Every prisoner has different levels of stress. This is caused by coping skills and the way of looking at the conditions of the problems faced, whether it is considered as a challenge or as a threat that has an impact on stress. This study aims to determine the relationship between coping mechanisms and stress levels in detainees in the detention house of the directorate of detention and evidence of the Central Kalimantan Regional Police. The research method is a quantitative design with a cross-sectional approach, the population is 54 prisoners, total sampling 54 respondents. Data were collected using a questionnaire. Data analysis using chi square test. The results showed that the statistical test obtained a value of ρ-value = 0.000 (<0.005) means that there is a relationship between coping mechanisms and stress levels in detainees at the detention center of the Central Kalimantan Regional Police detention and evidence directorate. It can be concluded, respondents with adaptive coping mechanisms were 34 prisoners (63%) while respondents with maladaptive coping mechanisms were 20 prisoners (37%), for respondents who had normal stress levels as many as 26 people (48.1%), mild stress levels 9 people (16.7%), moderate stress levels 13 people (24.1%) and severe stress levels 6 people (11.1%).